The value of models in informing resource allocation in colorectal cancer screening: The case of the Netherlands - Van Hees, F.; Zauber, A.; Van Veldhuizen, H.; Heijnen, M.; Penning, C.; De Koning, H.; Van Ballegooijen, M.; Lansdorp_Vogelaar, Iris (2015)
In May 2011, the Dutch government decided to implement a national programme for colorectal cancer (CRC) screening using biennial faecal immunochemical test screening between ages 55 and 75. Decision modelling played an important role in informing this decision, as well as in the planning and implementation of the programme afterwards. In this overview, we illustrate the value of models in informing resource allocation in CRC screening using the role that decision modelling has played in the Dutch CRC screening programme as an example.